(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background:Undergraduate students are one of the most vulnerable groups around the globe and the COVID-19 pandemic has had a major effect on their mental health. It is possible to produce accurate post-pandemic mental health estimates for KMU students, a significant but understudied group in the area, by using such an AKUADS instrument for anxiety and depression within a multi-institute framework. In the wake of the COVID-19 pandemic, this study sought to determine the incidence of mental health distress among undergraduates enrolled in KMU Peshawar main campus institutes in Peshawar and to explore associated factors. Methods: Undergraduates participating in Khyber Medical University’s allied health sciences programs were participants of this cross-sectional study. A validated AKUADS screening measure for depression and anxiety was utilized in the pre-structured questionnaire to collect the data. For the demographic data, SPSS version 24 was used to analyze the data using frequency and percentages; for associations, Pearson’s chi-square test with statistical significance set at p<0.05 was used Results: In total 324 students participated in the survey. Overall, 180 students (55·6%) tested positive for anxiety and depression. In comparison to male; female students were more prone to experience anxiety as well as depression. Participants from the Institute of Physical Medicine and Rehabilitation and Paramedical Sciences had lower odds to experience anxiety and depression. Participants reported having suicidal thoughts, with 7.7% indicating ongoing suicidal thoughts Age, year of study, place of residence, physical exercise, and social activity did not show any significant correlations. Conclusion: In the post-pandemic era, undergraduate health sciences students continue to experience significant rates of depression, anxiety, and suicide thoughts. In order to address psychological distress in this population, focused, institution-level mental health screening and support programs are necessary.